Computational Investigation of the Effect of Network Architecture on Mechanical Properties of Dynamically Cross‐Linked Polymer Materials. Issue 4 (26th April 2019) - Zanjani, Mehdi B.; Zhang, Borui; Ahammed, Ballal; Chamberlin, Joseph P.; Chakma, Progyateg; Konkolewicz, Dominik; Ye, Zhijiang
Abstract: Dynamically cross‐linked polymer networks have attracted significant interest in recent years due to their unique and improved properties including increased toughness, malleability, shape memory, and self‐healing. Here, a computational study on the mechanical behavior of dynamically cross‐linked polymer networks is presented. Coarse grained models for different polymer network configurations are established and their mechanical properties using molecular dynamics (MD) simulations are predicted. Consistent with the experimental measurements, the simulation results show that interpenetrating networks (IPN) withstand considerably higher stress compared to the single networks (SN). Additionally, the MD results demonstrate that the origin of this variation in mechanical behavior of IPN and SN configurations goes back to the difference in spatial degrees of freedom of the noncovalent cross‐linkers, represented by nonbonded interactions within the two system types. The results of this work provide new insight for future studies on the design of systems with dual dynamic cross‐linkers where one linkage exchanges rapidly and provides autonomic dynamic character, while the other is a stimulus responsive dynamic covalent linkage that provides stability with dynamic exchange on‐demand. Abstract : Dynamically cross‐linked polymer networks have attracted significant interest due to their unique and improved properties including increased toughness, malleability, shape memory, and self‐healing. A computational framework is established to explore the origin of significant differences in the mechanical behavior of various dynamically cross‐linked polymer materials, and the effect of network architecture on material properties is understood.